A 'Diplomatic Republic of Europe'? Explaining role conceptions in EU foreign policy. (June 2015) - Chelotti, Nicola
Using an original database of 138 questionnaires, the article explores how national officials perceive their role when participating in European Union (EU) foreign policy committees. It first shows that they systematically assume not only intergovernmental but also supranational role conceptions: a good number of diplomats understand EU foreign policy as a collective political project with the objective to craft a common European policy. The article then investigates some scope conditions. If the overall picture is complex and heterogeneous, it reveals that socializing activities occur in this policy field. More specifically, the number of years spent in Brussels is a relatively strong predictor of a supranational attitude. At the same time, diplomats' conceptions are formed also outside EU contexts: the structure and the pro-European opinions of the national polity affect the formation of a diplomat's orientation. Remarkably, member states' military power is a weak and non-significant variable in all the models tested.